Analisis Peran Digital dalam Peningkatan Penjualan Produk UMKM di CV. GTT Gudange Tahu Takwa Kabupaten Kediri - Auliya, Salma Mega; Suryani, Nining (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Digital marketing is defined as promotion and market search efforts carried out online using digital media, including social media and online networks. However, MSMEs in Kediri still face various obstacles, including the problem of low sales. Digital marketing provides opportunities for MSMEs to increase sales revenue. This research aims to explain the influence of digital marketing on increasing the income of MSMEs in Kediri. And it can also provide a deeper understanding of how digital marketing can be the key to success for MSMEs, especially in Kediri. By applying methods that describe digital marketing, MSME entrepreneurs can learn strategies for using digital technology to reach a wider audience and increase sales revenue. The results of the research show that digital marketing has a positive impact which is especially visible in increasing the sales turnover of MSMEs in Kediri. Factors in digital marketing that have a positive impact on increasing MSME sales in Kediri include choosing a social media platform, regularly updating information, and being responsive to customer needs. The aim of this research is not only for MSMEs in Kediri, but can also be a valuable guide for MSMEs in other places who face similar challenges. MSMEs can develop marketing strategies that are stable and develop their competitiveness in an increasingly competitive digital market.in an increasingly competitive digital market.